MicroRNAs of Human Herpesvirus 6A and 6B in Serum and Cerebrospinal Fluid of Multiple Sclerosis Patients - Domínguez-Mozo, María I.; Nieto-Guerrero, Alejandro; Pérez-Pérez, Silvia; García-Martínez, María Á.; Arroyo, Rafael; Álvarez-Lafuente, Roberto (Frontiers in Immunology, 2020)
Human herpesvirus-6A (HHV-6A) and -6B (HHV-6B) might be involved in the etiopathogenesis of multiple sclerosis (MS), specially the HHV-6A. We aim at assessing, for the first time in the scientific literature, the HHV-6A/B microRNAs in MS patients. We analyzed the miRNAs of HHV-6A: miR-U86, and -6B: hhv6b-miR-Ro6-1, -2, -3-3p, 3-5p, and -4 in paired samples of serum and CSF of 42 untreated MS patients and 23 patients with other neurological diseases (OND), using Taqman MicroRNA Assays. Intrathecal HHV-6A/B antibody production and anti-HHV-6A/B IgG/IgM levels in serum were measured. MS clinical data were available. We detected the following miRNAs: hhv6b-miR-Ro6-2 (serum: MS:97.7%, OND:95.7%; CSF: MS:81%, OND:86.4%), 3-3p (serum: MS:4.8%, OND:0%; CSF: MS:2.4%, OND:4.5%), 3-5p (serum: MS:95.2%, OND:91.3%; CSF: MS:50%, OND:54.5%), and miR-U86 (serum: MS:54.8%, OND:47.8%; CSF: MS:11.9%, OND:9.1%). In the CSF of patients with OND, the prevalence of hhv6b-miR-Ro6-2 (33.3%) in the intrathecal HHV-6A/B antibody production positive patients was significantly lower (p=0.038) than in the negative ones (94.7%). In MS patients, the prevalence of hhv6b-miR-Ro6-3-5p (87.5%) in the CSF of anti-HHV-6A/B IgG positive patients was significantly higher (p=0.044) than in the negative ones (40.6%); an inversed correlation between the levels of hhv6b-miR-Ro6-3-5p and anti-HHV-6A/B IgG (p=0.018 r=-0.512) was found in the CSF. The prevalence of miR-U86 (30.8%) in the CSF of individuals without gadolinium-enhancing lesions was higher (p=0.035) than in the ones with these lesions (0%). We propose a role of HHV-6A/B miRNAs in the maintenance of the viral latency state. Further investigations are warranted to study the association between miR-U86 and gadolinium-enhancing lesions.